University Students' Self-Medication Practices and Pharmacists' Role: A Cross-Sectional Survey in Hail, Saudi Arabia - Alshammari, Farhan; Alobaida, Ahmed; Alshammari, Abdulhadi; Alharbi, Atheer; Alrashidi, Adel; Almansour, Asma; Alremal, Amal; Khan, Kashif Ullah (Frontiers in Public Health, 2021)
Background: Self-medication is an important issue for health authorities around the world. It is also a common practice among university students. Objective: This study aimed to assess the prevalence of and reasons for self-medication among university students. Methods: A descriptive, cross-sectional community based survey design was adopted for the current study. All the students enrolled in Hail University, Saudi Arabia were selected to include in the study. Data was collected from February to April 2020 using a validated questionnaire and were analyzed using IBM SPSS Statistics, Version 22.0. Using convenient sampling technique, the total sample size calculated was 370 participants. A descriptive analysis was performed. Chi-square test and binary logistic regression was used for analyzing the data where statistical significance was set at p ≤ 0.05. Results: A total of 373 participants completed the questionnaire. The response rate was 84%. The overall prevalence of self-medication among the students was 98.2%. Of the 373 participants, 40.8% were men, and 59.2% were women. Furthermore, 56% were in fields other than health sciences, 23.1% were in preparatory foundation courses, and 20.9% were from the health and medical sciences. The most frequent medical condition that led to self-medication was headaches (92.85%), followed by coughs (37.5%), colic (31.9%) and influenza (30.3%). On univariate analysis, it is revealed that for both abdominal colic [OR 0.54 (0.34–0.86), p = 0.01] and constipation [OR 0.57 (0.32–1.02), p 0.05], female gender was observed significantly with low prevalence than male. However, for influenza, the self-medication prevalence [OR 1.86 (1.19–2.91), p = 0.006] observed was significantly higher in female participants than male. A significant association (p = 0.011) between the self-medication factors and gender was shown in the current study results. Conclusion: An alarming prevalence of self-medication among the students was recorded. Health care providers can increase awareness of the issue by educating individuals about the harmful effects of irresponsible self-medication.